Wonder drug : 7 scientifically proven ways that serving others is the best medicine for yourself - Trzeciak, Stephen; Mazzarelli, Anthony (St. Martin's Essentials, 2022)
"A pair of doctors team up to illuminate, through neuroscience and captivating stories from their clinical practice, how serving others-and pitching in to the world in general-is a secret superpower. If a doctor's prescription could bring you: - Longer life - Better health - More energy and resilience - Less burnout, depression and anxiety - More happiness, fulfillment and well-being - More personal and professional success (including higher income) - And, no harmful side effects Would you take it? In Wonder Drug, physician scientists Stephen Trzeciak, M.D., and Anthony Mazzarelli, M.D., illuminate, through neuroscience and captivating stories from their clinical practices, how being a giving, other-focused person is a secret superpower. Serving others-and pitching in to the world in general-is the evidence-based way to live your life. Kinder people not only live longer, they also live better. Science shows that serving others is not just the right thing to do, it's also the smart thing to do. Wonder Drug will make you rethink your notions of "self-care" and "me time," and realize that focusing on others is a potent antidote to the weariness that so many of us feel in modern times. Getting outside of your own head, outside the swirl of self-concern that may dominate your mental chatter, is, ironically, one of the best things you can do for yourself. Building upon their earlier work showing that, in the context of healthcare, having more compassion for patients is a powerful way to not only achieve better patient outcomes, but also promote well-being, resilience and resistance to burnout among healthcare workers, Trzeciak and Mazzarelli now extend their research to uncover how the power of serving others reaches far beyond the medical world and can be a life-changing therapy for everyone. Wonder Drug relates to the varying meanings of giving in real people's daily lives. The stories in this book will convince and inspire you to make simple prism changes. You don't need a total life upheaval, just a purposeful shift in mindset. In fact, the crucial first piece of the evidence-based prescription is this: start small. Per science, the best way to well-being and finding your true fulfillment is this: scan your orbit for the people around you in need of help, and go fill that need, as often as you can"--